The Impact of Innovation and Research and Development on the Transportation Performance: Moderating Role of Supply Chain Management - Hary Soegiri; Moeljadi Moeljadi; Sherlinda Octa Yuniarsa (International Journal of Supply Chain Management, 2020)
The aim attached to the study is to analyze the impact of innovation, innovation strategies and research and development on the transportation performance of Surabaya airport. The aim also includes the moderating impact of supply chain management among the links of innovation, innovation strategies, research and development and transportation performance. The data has been collected from the innovation department of Surabaya airport by using questionnaires and Smart-PLS has been employed for data analysis. The results exposed that positive nexus among the innovation, innovation strategies and research and development on the transportation performance of Surabaya airport. The results also revealed that supply chain management positively moderated among the links of innovation, innovation strategies and research and development and transportation performance of Surabaya airport. These findings are helpful for the management along with policymaking authorities that they should increase their emphasis on the innovation and research that enhance the performance of the transportation sector.